2005
DOI: 10.4310/atmp.2005.v9.n5.a1
|View full text |Cite
|
Sign up to set email alerts
|

One ring to rule them all and in the darkness bind them?

Abstract: We construct all eleven-dimensional, three-charge BPS solutions that preserve a fixed, standard set of supersymmetries. Our solutions include all BPS three-charge rotating black holes, black rings, supertubes, as well as arbitrary superpositions of these objects. We find very large families of black rings and supertubes with profiles that follow arbitrary closed curves in the spatial R 4 transverse to the branes. The black rings copiously violate black hole uniqueness. The supertube solutions are completely re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
617
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(629 citation statements)
references
References 44 publications
11
617
0
1
Order By: Relevance
“…The subject of supersymmetric black rings in the presence of a BMPV black hole was treated in [6] and the issue of adiabatic mergers of the ring with the black hole appeared in [22,23]. The authors, using the same embedding as presented here, found an exact BPS supergravity solution for the eleven dimensional lift of the black ring + black hole system; this solution can also be expressed in terms of Type IIA or IIB supergravity.…”
Section: Comparison Of Bena-kraus and Supergravity Supertubesmentioning
confidence: 91%
See 3 more Smart Citations
“…The subject of supersymmetric black rings in the presence of a BMPV black hole was treated in [6] and the issue of adiabatic mergers of the ring with the black hole appeared in [22,23]. The authors, using the same embedding as presented here, found an exact BPS supergravity solution for the eleven dimensional lift of the black ring + black hole system; this solution can also be expressed in terms of Type IIA or IIB supergravity.…”
Section: Comparison Of Bena-kraus and Supergravity Supertubesmentioning
confidence: 91%
“…There is another supertube for this background whose supersymmetric limit has {F zσ < 0, j 1 < 0, j 2 < 0}. 6 Unlike the other charges, q F 1 has a value that in general depends on the black hole charges, as well as the position and velocity of the supertube, as we will see in section 5. Its form in a BPS configuration is 17) where V 6 is the full spatial six-volume (2π) 6 R z 4 .…”
Section: Bena-kraus Supertubes Near a Bmpv Black Holementioning
confidence: 98%
See 2 more Smart Citations
“…Of course the multi-rings that we generate in this note by these methods, are by no means any new solutions which had previously been unheard of. For that matter, we point to some of the extensive literature, where several classes of 5D multi-center solutions have been worked out : [19], [24], [25], [26], [27]. The focus in this note is based more in the spirit of the box diagram in eq.…”
Section: Dmentioning
confidence: 99%